Nanotechnology-Based Diagnostic and Therapeutic Strategies for Neuroblastoma - Yan, Hui; Zhai, Bo; Yang, Fang; Chen, Zhenliang; Zhou, Qiang; Paiva-Santos, Ana Cláudia; Yuan, Ziqiao; Zhou, Yang (Frontiers in Pharmacology, 2022)
Neuroblastoma (NB), as the most common extracranial solid tumor in childhood, is one of the critical culprits affecting children's health. Given the heterogeneity and invisibility of NB tumors, the existing diagnostic and therapeutic approaches are inadequate and ineffective in early screening and prognostic improvement. With the rapid innovation and development of nanotechnology, nanomedicines have attracted widespread attention in the field of oncology research for their excellent physiological and chemical properties. In this review, we first explored the current common obstacles in the diagnosis and treatment of NB. Then we comprehensively summarized the advancements in nanotechnology-based multimodal synergistic diagnosis and treatment of NB and elucidate the underlying mechanisms. In addition, a discussion of the pending challenges in biocompatibility and toxicity of nanomedicine was conducted. Finally, we described the development and application status of nanomaterials against some of the recognized targets in the field of NB research, and pointed out prospects for nanomedicine-based precision diagnosis and therapy of NB.